Team up! Linking teamwork effectiveness of clinical teaching teams to residents' experienced learning climate. (2nd December 2019) - Jansen, Iris; Silkens, Milou E. W. M.; Stalmeijer, Renée E.; Lombarts, Kiki M. J. M. H.
Abstract: Background: Supportive learning climates are key to ensure high-quality residency training. Clinical teachers, collaborating as teaching team, have an important role in maintaining such climates since they are responsible for residency training. Successful residency training is dependent on effective teamwork within teaching teams. Still, it remains unclear whether this team effort benefits residents' perceptions of the learning climate. We, therefore, investigated to what extent teamwork effectiveness within teaching teams is associated with (1) the overall learning climate, and (2) its affective, cognitive and instrumental facets? Methods: This study used a web-based platform to collect data in clinical departments in the Netherlands from January 2014 to May 2017. Teamwork effectiveness was measured with the TeamQ questionnaire, administered amongst clinical teachers. The learning climate was measured with the D-RECT, applied amongst residents. Associations were analyzed using multilevel models and multivariate general linear models. Results: Teamwork effectiveness was positively associated with the overall learning climate as well as with the affective and the instrumental facets of the learning climate. No significant associations were found with the cognitive facet. Conclusion: Effective teamwork within teaching teams benefits learning climates in postgraduate medical education. Therefore, departments aiming to improve their learning climate should target teamwork within teaching teams.